2015
DOI: 10.1093/nar/gkv307
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging of duplex siRNA intracellular trafficking

Abstract: Intracellular distribution of siRNA after in vitro transfection typically depends on lipopolyplexes, which must release the siRNA into the cytosol. Here, the fate of siRNAs was monitored by FRET-based live cell imaging. Subsequent to in situ observation of uptake and release processes, this approach allowed the observation of a number of hitherto uncharacterized intracellular distribution and degradation processes, commencing with a burst of endosomal releases, followed, in some cases, by fast siRNA influx int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Application of different siRNA complexes with lipids and polymers faces with the need to address different requirements for effective formation of the complex, its stability in serum, and effective release from the endosome, which necessitates construction of multilevel structures 40 . The issue of toxicity is also very important 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of different siRNA complexes with lipids and polymers faces with the need to address different requirements for effective formation of the complex, its stability in serum, and effective release from the endosome, which necessitates construction of multilevel structures 40 . The issue of toxicity is also very important 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, siRNA within the cell is isolated from the cytoplasm by the endosomal membrane 40 . Endosomal escape is a limiting step in achieving effective gene silencing 59 .…”
Section: Discussionmentioning
confidence: 99%
“…A fraction of the siRNA translocate into the nucleus, which is in accordance with a previous report. 31 A very small fraction of the siRNA remains complexed with streptavidin and entrapped in lysosomes. A significant amount of siRNA and nanocomplex are exocytosed, which may explain the transient silencing activity of synthetic siRNA delivered by nonviral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…37, 38 In accordance with our results, several other groups also demonstrated that siRNA alone can translocate inside and out of the nucleus. 31, 39 …”
Section: Discussionmentioning
confidence: 99%
“…Editorial kinetic parameters associated with siRNA diffusion, dissociation and degradation [17]. Using FRET-labeled siRNA as a method for assaying siRNA integrity, it was shown that the cytoplasmic delivery of siRNA is accomplished by burst release from endosomal vesicles [18].…”
Section: Fluorescence Microscopymentioning
confidence: 99%